Analysis of the Impact of Lies on Children's Trust in Adults - Aulia, Hafidzatul; Khan, Omar; Wei, Li (Yayasan Minang Darussalam, 2024)
Trust is an important aspect of early childhood social and emotional development, which is formed through interactions with authority figures such as parents and educators. However, lies told by adults, whether with protective or disciplinary intentions, can affect children's trust. This study analyzes the impact of lies on early childhood trust in adults through a literature review. Using literature analysis from various sources, this study found that lies, especially if repeated, can damage children's trust, hinder the formation of healthy emotional relationships, and affect children's ability to distinguish between honesty and lies. In addition, the type of lie has different impacts; lies with good intentions can produce milder effects than lies for personal gain. Long-term impacts include the tendency for children to imitate lying behavior and impaired social development. This study recommends the importance of honest communication by parents and educators to build strong children's trust, as well as the need for further studies to explore other factors, such as culture and parenting, that can moderate the relationship between lies and trust. These findings are expected to contribute to developmental psychology and become practical guidelines in supporting the formation of children's trust without using lies.